INTEGRATED MADRASAH DINIYAH TAKMILIYAH MODEL IN ELEMENTARY SCHOOL IN MADRASAH DINIYAH TAKMILIYAH AWALIYAH (MDTA) MUHAMMADIYAH 12 MEDAN - Mardianto Mardianto; Khadijah Khadijah; Ilham Agam Setiawan (Universitas Dharmawangsa Medan, 2021)
The purpose of this research is to analyze the implementation of Integrated Madrasah Diniyah Takmiliyah Awaliyah in Elementary Schools at Madrasah Diniyah Takmiliyah Awaliyah Muhammadiyah 12 Medan, analyzing the results of the quality achievements of the Integrated Madrasah Diniyah Takmiliyah Awaliyah and Primary Schools Muhammadiyah 12 Medan, as well as the supporting and inhibiting factors of the Integrated Madrasah Diniyah Takmiliyah Awaliyah at Madrasah Diniyah Takmiliyah Awaliyah Primary School Muhammadiyah 12 Medan. This study uses a qualitative research method, which is a study that aims to understand the phenomena experienced by the research subject including behavior, perception, motivation, action and others, holistically and by means of descriptions in the form of words and language, at a special context that is natural by utilizing various natural methods, in a real field situation which is natural as it is without manipulation. The results of this study indicate that: (1) Implementation of Integrated Madrasah Diniyah Takmiliyah Awaliyah in Primary Schools at Madrasah Diniyah Takmiliyah Awaliyah Muhammadiyah 12 Medan, (2) Management of Integrated Madrasah Diniyah Takmiliyah Awaliyah in Primary Schools at Madrasah Diniyah Takmiliyah Awaliyah Muhammadiyah 12 Medan, (3) Results of the quality achievements of Integrated Madrasah Diniyah Takmiliyah Awaliyah at Madrasah Diniyah Takmiliyah Awaliyah Primary School (MDTA) Muhammadiyah 12 Medan, (4) Supporting and inhibiting factors for Integrated Madrasah Diniyah Takmiliyah Awaliyah in Madrasah Diniyah Takmiliyah Awaliyah Primary School Muhammadiyah 12 Medan.